PENGARUH APLIKASI TOPIKAL MADU, GEL ALOE VERA, DAN MOIST EXPOSED BURN OINTMENT (MEBO) Terhadap Kepadatan Fibroblas Pada Proses Penyembuhan Luka Bakar Derajat II Tikus (Rattus Norvegicus) - Ajeng Ratna Haryanti, (2020)
Burn injury is a traumatical event that can destruct skin tissue. It can be measured by its severity that consists 1st degree (superficial), 2nd degree (partial thickness), and 3rd degree (full thickness). Migration of fibroblast is the main process on wound healing. Honey, Aloe vera gel, Moist Exposed Burn Ointment (MEBO) have the potential on wound healing as their anti-inflamatory effect. This study aimed to determine the effect of topical application of honey, Aloe vera, and MEBO on fibroblast density. There are 28 rats that were divided into four group of treatment; (1) burn rats with topical application of NaCl 0,9% twice a day, (2) burn rats with topical application of honey twice a day, (3) burn rats with topical application of Aloe vera twice a day, (4) burn rats with topical application of MEBO twice a day. The treatments were given for 6 days to the burn rats. This study was analyzed by One Way ANOVA and continued with Post-Hoc Bonferroni. In conclusion, topical application of honey is the most effective to increase fibroblast density on wound healing process in second degree burn rats.